(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
Modern ststae of invasive european bream (Abramis brama) was studied in Tudakul reservoir (lower stream of Zarafshen River) in 2020-2022. Fins rays formula was D II 9 - 10, A (I) II 24-27;47-54 scalesin lateral lineand 19-21gil rakers were determined. Plastic indexes according to tradinional for cyprinids so as indexes of «truss protocol» are given. A significant difference in the value of a number of plastic indexes was revealed between immature and matured european bream. The ages of the samples ranged between 1 to 5 years, the total length 144.3 – 444.9 mm, the standard lengths 113.3 – 337.0 mm and total weights 27.0 – 845.1 g. The relationship between the total length (TL) and weight (W) was described by W = 0,0436*TL2,7925 (r=0,98). The mean back calculated total length was 13.2 cm at age I; 23.3 cm, II; 30.1 cm, III; 43.4 cm, IV; 44.0 cm.